Monitoring load, wellness, and psychological variables in female and male youth national team football players during international and domestic playing periods - Andersen, Thomas Rostgaard; Kästner, Bennet; Arvig, Mathias; Larsen, Carsten Hvid; Madsen, Esben Elholm (Frontiers in Sports and Active Living, 2023)
Aim: To study differences in total load exposure, wellness, and psychological variables in youth female (N=19) and male (N=20) national team football players duringdomestic and international playing periods, respectively. Procedures: The players filled out questionnaires on well-being, stress, and resilience before and after both playing periods lasting 8 days each. The Hooper index was used to monitor daily wellness levels during both playing periods. The number of training sessions and matches were recorded, and the session rating of perceived exertion was collected. Training load, monotony, and strain were calculated. Daily measurements were used to evaluate in-period changes, and composite scores were used to describe differences between periods. Results: The international compared to the domestic playing period was for both groups characterized by more matches played, longer field training session durations, and of fewer gym-based sessions (P<0.05). The male players increased total exposure time (25%; P<0.05), monotony (P<0.001), and strain (P<0.001), which was not changed in the female players. Well-being decreased (P<0.05) during the international playing 2 This is a provisional file, not the final typeset article period in male players. Stress levels were higher (P<0.05) for both genders during the international compared to the domestic playing period. During the international playing period, positive correlations were found between the initial levels of stress, and the change in stress (P=0.03; r 2 =0.12), and between the changes in total load and changes in well-being (P=0.02; r 2 =0.12), whereas a negative correlation was found between the changes in wellness and stress (P=0.03; r 2 =0.14). Conclusion: A playing period characterized by increased match focus, longer field training sessions, and fewer gym-based training activities may lead to changes in the physical and mental profiles of youth national team football players. Alterations to load exposure and wellness may influence mental health. Players with high initial stress levels may be subjected to greater changes compared to other players. Sports scientists and medical staff may benefit from initiating structured monitoring systems to track alterations in physical load and mental health in youth national team players.